The financial impact of sheep theft in the Free State Province of South Africa - Lombard, Willem Abraham (University of the Free State, 2016)
In South Africa, livestock theft is nothing new to farmers and is considered by some to be as old as farming itself. Recorded cases of livestock theft in South Africa can be traced as far back as 1806. Livestock theft affects the livestock industries in all nine provinces of South Africa, with stock theft being a priority crime in most of the provinces. Livestock theft is not a unique problem that is confined to South Africa or even Africa. Available studies on livestock theft have only focused on the direct cost of losses. However, no study has been done to quantify the direct, as well as indirect cost of livestock theft in the Free State Province of South Africa. Indirect cost represents the cost of loss-controlling practices performed by farmers against livestock theft. The primary objective of this report is to quantify the financial impact or implications of sheep theft in the Free State Province of South Africa. Secondary objectives include the distinguishing of direct and indirect costs of livestock theft. It was also deemed important to identify variables affecting sheep livestock theft in the Free State Province. Investigation of the variables will help to better understand the occurrence of livestock theft in the Free State Province. This survey was conducted in the Free State Province of South Africa and included respondents from all five of the district municipalities. The sample used consisted of 292 respondents representing 159 081 sheep or 3.31% of the sheep in the Free State Province. A structured questionnaire was used to collect the data during telephonic interviews with livestock farmers. The questionnaire included questions on topographic factors, demographic factors, and the control practices that farmers are using to protect their livestock. All five of the district municipalities are affected by livestock theft with the highest annual loss rate occurring in the Lejweleputswa district (5.98%) and the lowest annual loss rate occurring in the Xhariep district (0.96%). It was found that 84 955 sheep are annually lost to stock theft in the Free State Province. To put this in perspective, this number is more than four times the number shown in official statistics. The total annual direct cost of livestock theft in the Free State Province is estimated at R144 423 500. The total annual indirect cost of livestock theft (control practices) was determined at R38 536 894. Therefore, the total annual cost of livestock theft in the Free State Province is estimated at R182 960 394. The data were used to investigate the variables affecting livestock theft. A Tobit (level), Probit (occurrence) and Truncated (level) model was used to identify variables associated with the occurrence and level of livestock theft experienced. The Craggs test was used to determine whether the variables affecting the occurrence of livestock theft are significantly different from the variable affecting the level of livestock theft experienced. The Granger Causality test was used to determine the direction of causality for variables that had a significant relationship with livestock theft. The results suggest that the longer farmers take to report stock theft cases, the more likely they are to experience stock theft. It was also determined that some farmers are taking longer to report cases due to the high level of stock theft they experience. In some cases where sheep are corralled at night in an attempt to control the occurrence of livestock theft, it has also led to higher occurrence rates of stock theft. Farmers near the Lesotho border experience stock theft on a more regular basis than the rest of the Free State Province, though not at higher levels. The information that was collected during the study confirms that livestock theft has a major impact on the livestock industry in the Free State Province. Also, official stock theft statistics do not accurately represent the actual losses experienced by farmers. This study does not provide all the answers to the problem; however, valuable information regarding the direct and indirect cost was determined as well as some variables affecting livestock theft. If similar research could be done in other parts of the country, the findings could serve as guidelines to livestock owners across South Africa to control livestock theft.
Keywords: Livestock theft; Direct cost; Indirect cost; Total cost; Internal variables; External variables; Sheep -- South Africa -- Free State; Livestock -- South Africa -- Free State; Theft -- South Africa -- Free State; Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2015